COLLABORATIVE GOVERNANCE REGIME DALAM PENYELESAIAN KONFLIK LAHAN MANDALARE DI KOTA BANJAR - Septian Lestari; Riza Purnama; Talbiyah Noer M; Tina Cahya Mulyatin (Program Studi Ilmu Pemerintahan FISIP Universitas Galuh, 2026)
Land conflicts in the Mandalare area of Banjar City reflect the complexity of the relationship between the government and the community in the context of resource management. Issues arise due to differing perceptions regarding land status and use, which have not been addressed through equitable dialogue mechanisms. This study aims to analyze the application of collaborative governance in resolving land conflicts and to identify factors influencing its effectiveness. The method used is a qualitative approach with data collection techniques through interviews, observations, and documentation, analyzed using a descriptive-interpretive approach. The results indicate that collaboration has not been optimal, characterized by limited substantive engagement, low trust among actors, and the absence of a structured capacity for collective action. The study’s conclusion emphasizes that conflict resolution requires strengthening the dialogue process, information transparency, and sustainable collaborative institutions. The novelty of this research lies in its integrative analysis based on the collaborative governance framework, which not only assesses the formal aspects of collaboration but also emphasizes the relational dynamics among actors as the key to sustainable and context-specific conflict resolution.